China and India challenges and opportunities for ASEAN from Japanese perspectives - Okamoto, Yumiko (The Philippine Review of Economics, 2006)
The rise of China and India as industrial powers is now regarded as an opportunity rather than a threat for member countries of the Association of Southeast Asian Nations (ASEAN). The paper shows that whether or not this view is consistent with the underlying economic forces depends on the country in question. Singapore and Malaysia seem to gain through inter- and intra-industry specialization if a free trade agreement (FTA) is formed between ASEAN and China. Thailand appears to gain significantly through intra-industry specialization vis-à-vis China. An FTA between ASEAN and China may significantly impact Japan as well, since Japanese companies have heavily invested in these two regions for the past three decades. The promotion of economic cooperation between ASEAN and India, on the other hand, may make sense in the long run, but its immediate impact on both sides as well as on Japan still seems to be limited.